LEGAL PROTECTION FOR PATIENTS OF HEALTH SERVICES AT RSUD ARGA MAKMUR BASED ON LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION AND LAW NO. 25 OF 2009 CONCERNING PUBLIC SERVICES. - Erni Sisna Wati; Slamet Muljono; Widiya N. Rosari (Bengkoelen Justice : Jurnal Ilmu Hukum, 2022)
This study examines the legal protection of patients as consumers of health services at RSUD Arga Makmur. This study aims to determine the legal protection of patients as consumers of health services and factors that support or hinder the legal protection of patients in RSUD Arga Makmur. In this study, the author examined the extent to which legal protection for patients of health services was carried out by health personnel in hospital. With the sociological juridical method, the author examines the legal protection of patients by considering the extent to which the patient's rights are fulfilled by health workers and hospital. The results showed that the legal protection of patients as consumers of health services at RSUD Arga Makmur is considerably good. The factors that hinder and support consist of internal and external factors which include communication, information, legal awareness, hospital facilities, work environment, and attitudes from the patient.